Chronic Pain After Spinal Cord Injury: Is There a Role for Neuron-Immune Dysregulation? - Chambel, Sílvia S.; Tavares, Isaura; Cruz, Célia D. (Frontiers in Physiology, 2020)
Spinal cord injury (SCI) is a devastating event with a tremendous impact in the life of the affected individual and family. Traumatic injuries related to motor vehicle accidents, falls, sports and violence are the most common causes. The majority of spinal lesions is incomplete and occurs at cervical levels of the cord, causing a disruption of several ascending and descending neuronal pathways. Additionally, many patients develop chronic pain and describe it as burning, stabbing, shooting, or shocking and often arising with no stimulus. Less frequently, people with SCI also experience pain out of context with the stimulus (e.g., light touch). While abolishment of the endogenous descending inhibitory circuits is a recognized cause for chronic pain, an increasing number of studies suggests that uncontrolled release of pro- and anti-inflammatory mediators by neurons, glial and immune cells is also important in the emergence and maintenance of SCI-induced chronic pain. This constitutes the topic of the present mini-review, which will focus on the importance of neuron-immune dysregulation for pain after SCI.